2015
DOI: 10.3892/ol.2015.3587
|View full text |Cite|
|
Sign up to set email alerts
|

miR-215 functions as a tumor suppressor and directly targets ZEB2 in human non-small cell lung cancer

Abstract: MicroRNA-215 (miR-215) has previously been demonstrated to be dysregulated in a number of human malignancies and to be correlated with tumor progression. However, the expression and function of miR-215 in non-small cell lung cancer (NSCLC) has remained to be elucidated. Therefore, the present study aimed to investigate the effects of miR-215 in NSCLC tumorigenesis and development. Reverse transcription-quantitative polymerase chain reaction was used to evaluate miR-215 expression in NSCLC cell lines and primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
35
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 39 publications
9
35
2
Order By: Relevance
“…Several targets of miR-215 have been identified, including runt-related transcription factor 1 (28) and RB transcriptional corepressor 1 (26) in gastric cancer, X-linked inhibitor of apoptosis in epithelial ovarian cancer (30), and zinc finger E-box binding homeobox 2 in pancreatic cancer (31) and non-small cell lung cancer (32). In our study, AKT1 was validated as a novel target of miR-215 through four experiments.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Several targets of miR-215 have been identified, including runt-related transcription factor 1 (28) and RB transcriptional corepressor 1 (26) in gastric cancer, X-linked inhibitor of apoptosis in epithelial ovarian cancer (30), and zinc finger E-box binding homeobox 2 in pancreatic cancer (31) and non-small cell lung cancer (32). In our study, AKT1 was validated as a novel target of miR-215 through four experiments.…”
Section: Discussionmentioning
confidence: 75%
“…The expression level of miR-215 was demonstrated to be associated with the International Federation of Gynecology and Obstetrics stage, the histological grade, and the extents of vascular invasion and lymph node metastasis of cervical cancer; the 5-year survival rate was lower in patients with stage II cervical cancer who exhibited miR-215 overexpression (29). However, previous studies have also demonstrated that miR-215 may be downregulated in epithelial ovarian (30), pancreatic (31), non-small cell lung (32), breast (33) and colon (34) cancer. In the study on pancreatic cancer, a low expression level of miR-215 was significantly associated with a large tumor size, an advanced TNM stage, a high extent of lymph node metastasis and vessel invasion, and lower overall survival time; multivariate regression analysis demonstrated that miR-215 underexpression was an independent unfavorable prognostic factor for patients (31).…”
Section: Discussionmentioning
confidence: 96%
“…Decreased levels of miR-215-5p measured both in tissue and serum, have been reported in metastatic breast cancer patients as compared to non-cancerous controls [30]. In a study of NSCLC, miR-215-5p was down-regulated in lung tumor tissue as compared to adjacent lung tissue, and over-expression of miR-215-5p inhibited progression of lung cancer [31]. This is in line with our study, as low levels of miR-215-5p were associated with decreased OS, which may be explained by the hampered tumor suppressor effect of miR-215-5p.…”
Section: Discussionmentioning
confidence: 98%
“…Increasing studies have demonstrated that microRNAs (miRNAs/miRs) have vital functions in numerous developmental processes and tumorigenesis, including the progression of NSCLC (6)(7)(8). miRNAs represent a group of small (~19-25 nucleotides), non-protein-coding, and endogenous single RNAs, which negatively regulate gene expression by binding to the 3' untranslated regions (3'UTRs) of target genes in an imperfect base pairing manner, causing mRNA cleavage or translational repression (9,10).…”
Section: Introductionmentioning
confidence: 99%